Comparison of trace element concentrations in paired formalin-fixed paraffin-embedded and frozen human placentae. (January 2023) - Coyte, Rachel M.; Darrah, Thomas H.; Barrett, Emily; O'Connor, Thomas G.; Olesik, John W.; Salafia, Carolyn M.; Shah, Ruchit; Love, Tanzy; Miller, Richard K.
Abstract: Introduction: There is increasing interest in measuring metals concentrations in human placentas to better understand physiology, disease, and toxic and diagnostic exposures. For these purposes, formalin-fixed paraffin embedded (FFPE) tissues obtained at clinical pathology examination represent a valuable potential store of well-characterized tissues for analysis. However, the limited data that exist comparing metal concentrations in FFPE tissue to recently collected frozen tissues paints a confusing picture, and there is no published data directly comparing frozen and FFPE placental villus tissues. Methods: Paired samples of fresh frozen and FFPE tissue from 22 rapidly processed human singleton placentae were weighed and digested using standard clean laboratory procedures and subsequently analyzed for a suite of 13 metals using a PerkinElmer DRC II ICP-MS . The analytical results were compared using either a paired t -test or a sign test depending on data normality. Results: Concentrations of metals (aluminum (Al), arsenic (As), barium (Ba), cadmium (Cd), chromium (Cr), copper (Cu), iron (Fe), gadolinium (Gd), mercury (Hg), manganese (Mn), lead (Pb), strontium (Sr), and zinc (Zn)) measured in both types of tissue preparations (frozen and FFPE) displayed a consistent range with other studies and did not display significantly different values from each of the paired specimens for any of the 13 specific metals analyzed. Discussion: Within placentae, metals concentrations of measured trace, toxic and diagnostic elements (Al, As, Ba, Cd, Cr, Cu, Fe, Gd, Hg, Mn, Pb, Sr, and Zn) are consistent between FFPE and fresh placental villus tissue, without indications of systematic element loss or bias. FFPE from archived pathology specimens may offer an important and convenient alternative for measuring trace metals in human frozen placental tissues. Highlights: Metals in human placentae portend important exposures prior to/during pregnancy. Toxic metals are identified in formalin-fixed, paraffin embedded placentae. Formalin-fixed placenta from pathology allows for accurate toxic metal assessments. Examples include lead, cadmium, mercury, arsenic, MRI contrast – gadolinium, among other metals.